158 Virtual Interactive Surgical Skills Classroom: A Parallel-Designed, Non-Inferiority, Adjudicator-Blinded, Randomised Controlled Trial (VIRTUAL). (19th August 2022) - Fricker, Monty; Nathan, Arjun; Georgi, Maria; Patel, Sonam; Kien, Man Kien; Asif, Aqua; Sinha, Amil; Mullins, William; Shea, Jessie; Hanna, Nancy; Monks, Massimo; Peprah, David; et al.
Abstract: Introduction: Virtual classroom training (VCT) is a novel educational method that permits accessible, distanced interactive expert instruction. We aimed to evaluate the efficacy of VCT in comparison to face-to-face training (FFT) and non-interactive computer-based learning (CBL) for basic surgical skills training. Method: 72 participants recruited from five London medical schools underwent stratified block randomisation into three equal intervention groups based on subjective and objective suturing experience. VCT was delivered via the BARCO weConnect platform and FFT was provided by expert instructors. Optimal student-to-teacher ratio was used, 12:1 for VCT and 4:1 for FFT. The assessed task was interrupted suturing with hand-tied knots. The primary outcome was post-intervention Objective Structured Assessment of Technical Skills (OSATS) score, adjudicated by two blinded experts and adjusted for baseline proficiency. Results: VCT was non-inferior to FFT (adjusted difference 0.44, 95% CI: -0.54 to 1.75, delta 0.675), VCT was superior to CBL (adjusted difference 1.69, 95% CI 0.41 to 2.96) and FFT was superior to CBL (adjusted difference 1.25, 95% CI 0.20 to 2.29). FFT alone was associated with student travel expenses (mean £4.88, SD 3.70). Instructor hours used per student for VCT and FFT were 0.25 and 0.75, respectively. Conclusions: VCT has a similar educational benefit to FFT and is a suitable modality of high-quality surgical skills education. VCT provides greater accessibility and resource efficiency compared to FFT. VCT satisfies the requirement for social distancing during the COVID-19 pandemic and is better than non-interactive CBL. VCT has the potential to improve global availability and accessibility of surgical skills training.